Gambaran pengelolaan posyandu oleh kader di Kecamatan Cikampek, Kabupaten Karawang Tahun 2019 - Dani Ferdian; Tessa Melinda Agatta; Fedri Ruluwedrata Rinawan; Didah; Dwi Agustian (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to find a management overview of posyandu by cadres and characteristics of posyandu cadres in Cikampek District, Karawang. Method: This study used a quantitative descriptive design study. The subjects of the study were 65 posyandu cadres. From 65 research subjects, 59 research subjects met the inclusion criteria. The research instrument used was secondary data. Result: The result of the study show that the characteristics of research subjects are mostly 36-45 years old (49.15%), have studied up to senior high school (74.58%), have served as posyandu cadres for 1-5 years (57.63%) ), have received training 1-2 times (54.24%), have good knowledge about posyandu (64.41%), and have the motivation to participate in public health services (67.80%). Posyandu services provided are good (38.98%) and very good (30.51%). This good service is supported by the very good participation of cadres in posyandu activities (52.54%). In terms of data reporting, 89.83% reported monthly Posyandu data. In the implementation of the activity, 30.50% of the posyandu collaborated with CSR, while most of them did not know that there was cooperation with other parties (33.90%). And there is 45.76% of posyandu with madya strata. Conclusion: Posyandu services carried out by cadres in Cikampek District, Karawang Regency have shown good and very good results, but more effective cooperation is still needed from other parties participating in posyandu activities. This good posyandu service is supported by cadre knowledge, cadre performance, work experience, cadre motivation to build posyandu, as well as by the existence of training attended by cadres.